7 - Book Reviews: Steven Feierman, Peasant Intellectuals: Anthropology and History in Tanzania, University of Wisconsin Press, Madison, 1990, pp.340. - Zeleza, Paul Tiyambe (Africa Development, 1993)
Abstract